2012
DOI: 10.1111/j.1476-5381.2011.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conduction along endothelial cell tubes from mouse feed arteries: confounding actions of glycyrrhetinic acid derivatives

Abstract: BACKGROUND AND PURPOSEElectrical conduction along endothelium of resistance vessels has not been determined independently of the influence of smooth muscle, surrounding tissue or blood. Two interrelated hypotheses were tested: (i) Intercellular conduction of electrical signals is manifest in endothelial cell (EC) tubes; and (ii) Inhibitors of gap junction channels (GJCs) have confounding actions on EC electrical and Ca 2+ signalling. EXPERIMENTAL APPROACHIntact EC tubes were isolated from abdominal muscle feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
110
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(119 citation statements)
references
References 46 publications
9
110
0
Order By: Relevance
“…Previous reports showed that glycerophosphatidylcholine concentration typically increases with age; moreover, this increase is more pronounced in aged AD patients and those with enhanced A ␤ plaque formation (29)(30)(31)(32). Breakdown of APP and aggregation of amyloid plaques are the major causes of neuronal deterioration in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that glycerophosphatidylcholine concentration typically increases with age; moreover, this increase is more pronounced in aged AD patients and those with enhanced A ␤ plaque formation (29)(30)(31)(32). Breakdown of APP and aggregation of amyloid plaques are the major causes of neuronal deterioration in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of inhibitors of gap junctions are widely used but are generally considered to be nonspecific, and their mechanism of inhibition have not been clearly defined (Evans and Boitano, 2001;Evans et al, 2012). For example, studies of the functional role of connexins in arterioles have extensively used inhibitors such as glycyrrhetinic acid and carbenoxolone, but recent studies have identified nonspecific effects of these blockers, including inhibition of calcium-activated potassium channels (Behringer et al, 2012). The development of transgenic animals was first thought to be a solution to cope with the lack of specific pharmacological inhibitors, but it is now clear that a number of compensations and/or redistribution of other connexin isoforms occur in Cx KO animals, which could further hinder interpretation of connexins on physiologic function (e.g., Kruger et al, 2002;Simon and McWhorter, 2003;Isakson et al, 2006a).…”
Section: Physiologic Function Referencesmentioning
confidence: 99%
“…b Evidence that although connexin expression and/or gap junction communication levels correlated to disease they do not appear to be directly linked to phenotypic modulation (Matsushita et al, 2007;Behringer et al, 2012).…”
Section: Physiologic Function Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEA is dissected free from surrounding skeletal muscle fibers and connective tissue, blood is flushed from the lumen, and mild enzymatic digestion is performed to enable removal of adventitia, nerves and smooth muscle cells using gentle trituration. These freshly-isolated preparations of intact endothelium retain their native morphology, with individual ECs remaining functionally coupled to one another, able to transfer chemical and electrical signals intercellularly through gap junctions 6,7 . In addition to providing new insight into calcium signaling and membrane biophysics, these preparations enable molecular studies of gene expression and protein localization within native microvascular endothelium.…”
mentioning
confidence: 99%